Social Demography Study of Gonorrhea and Syphilis at RSUD dr. Soedono Madiun - Rahajeng Musy; Vita Widyasari; Rosmelia Rosmelia (Universitas Muhammadiyah Yogyakarta, 2019)
An understanding of the socio-demographic characteristics is the first step to conduct preventive and promotive measures to reduce the number of sexually transmitted infections. This study described the socio-demographic cha-racteristics of gonorrhea and syphilis in dr. Soedono Hospital Madiun. A descripttive study with a quantitative approach used secondary data from outpatient medical records. This research was conducted in dr. Soedono Hospital Madiun, East Java. The samples used in this study were 61 patients who had been diagnosed with gonorrhea and syphilis in the period from July 2013 - June 2016. The data consisted of 50 (82%) medical records with the diagnosis of gonorrhea and 11 (18%) medical records with a diagnosis of syphilis. Characteristics of patients/respondents are the highest age group of 21-30 years, 22 female patients (36.1%), 55 male patients (90.2%), unmarried status 33 people (54.1%), work as private employees 37 people (60.7%), pay without insurance 48 people (78.7%), and live around Madiun 52 (86.0%). The socio-demographic factors were dominant in patients with gonorrhea and syphilis in dr. Soedono Hospital period of 2013-2016 was 21-30 years old, male, unmarried, living as private sector employees, pay without insurance, and Madiun origin.